Endemicity Analysis of the Ichtyofauna of the Rio Doce Basin, Southeastern Brazil - Sarmento Soares, Luisa M. (2022)
The Rio Doce is a very important freshwater system in Brazil running through the Atlantic Forest, however available information about its biodiversity is scarce. In 2015, the Rio Doce basin was damaged by a burst of Fundão tailing dam in Mariana (Minas Gerais) causing an extraordinary environmental damage, with consequences still incompletely known. In the present paper we analyzed 6042 latitude/longitude records of 208 fish species from the Rio Doce deposited in collections prior to November 2015, in order to identify areas of endemism in the river before the burst. Several areas of endemism were identified along the basin, most of them describing small and novel patterns. Our analyses helped to identify areas of major diversity along the basin as well as information gaps concerning fish sampling. We hope this contribution will help obtaining quantitative measures on the impact caused by the Fundão dam catastrophe on fish biodiversity and will be useful to orient general actions towards the restoration of the basin.